Phenotype Characteristics of Kampung Chicken in Dullah Selatan District Tual Regency - Abdul M. Jaimiri; Bercomien J. Papilaya; Rajab Rajab (Universitas Pattimura, 2023)
Qualitative and quantitative traits are used to identify chicken lines, and in breeding qualitative and quantitative traits can be used to produce superior breeds of chickens. In this study, the authors aimed to determine the phenotype (qualitative and quantitative characteristics) of chickens in Dullah Selatan, Tual City. The results of this study found that the qualitative characteristics of native chickens were feather color: white (8 males (11.59%) and 5 females (6.76%), black (0 males (0.00%) and 29 females ( 39.19%), liars (6 males (8.70%) and 8 females (10.81%), Columbia (50 males (72.46%) and 24 females (32.43%), and striated (5 males (7.25%) and 8 females (10.81%); comb form: single (41 males (59.42%) and 42 females (56.76%) and pea (male) 28 individuals (40.58%) and 32 females (43.24%); and shank color: Black/gray (8 males (11.59%) and 37 females (50.00%) and yellow/white (61 males (88.41%) and 37 females (50.00%) While quantitative characteristics were found on average body weight: Males 1338.07 g and females 964.87 g Chest circumference: Males 27 .01 cm and female 24.55 cm; Upper thigh length: Male 9.44 cm and female 8.03; Lower thigh length: male 13.15 cm and female 11.6; Shank length male 10.28 cm and female 8.08 cm.